Marketing System for Rumah Coklat Trenggalek Based on Website, Online Store, and Game as I.T. Ecosystem - Pratama Wirya Atmaja; Sri Wiyatiningsih (Future Science)
CV. Rumah Coklat is a new company in Trenggalek, East Java, that is in the business of production and retail selling of chocolate in cooperation with local government and cacao farmers. Because of its status as a new company and its location in Trenggalek, which is not a big city, CV. Rumah Coklat faces significant difficulties in marketing its products. To improve the situation, Technopark UPN “Veteran” of East Java is incubating CV. Rumah Coklat in order to develop its online marketing system which consists of a website, an online store, and a game application. The three elements of the marketing system are integrated and therefore are able to exchange information with other for various purposes. The game application is a freemium, which means it can be downloaded and played freely but requires the players to unlock features by buying products on the online store, and this in turn will boost CV. Rumah Coklat’s revenue as the game application’s players become potential consumers for the chocolate products. Other than that, the game application can also show advertisements for products that are being sold on the online store, give vouchers or prizes to the best players which can be redeemed on the online store, and other things that can increase brand awareness and consumer engagement. The website and the online store have been launched and the 1.0 version of the game application will be released for Android platform on Google Play Store